The evolution of sex chromosome dosage compensation in animals. (20th November 2020) - Chen, Jiabi; Wang, Menghan; He, Xionglei; Yang, Jian-Rong; Chen, Xiaoshu
Abstract: The evolution of heteromorphic sex chromosomes shall lead to gene expression dosage problems, as in at least one of the sexes, the sex-linked gene dose has been reduced by half. It has been proposed that the transcriptional output of the whole X or Z chromosome should be doubled for complete dosage compensation in heterogametic sex. However, owing to the variability of the existing methods to determine the transcriptional differences between sex chromosomes and autosomes (S:A ratios) in different studies, we collected more than 500 public RNA-Seq data set from multiple tissues and species in major clades and proposed a unified computational framework for unbiased and comparable measurement of the S:A ratios of multiple species. We also tested the evolution of dosage compensation more directly by assessing changes in the expression levels of the current sex-linked genes relative to those of the ancestral sex-linked genes. We found that in mammals and birds, the S:A ratio is approximately 0.5, whereas in insects, fishes, and flatworms, the S:A ratio is approximately 1.0. Further analysis showed that the fraction of dosage-sensitive housekeeping genes on the X/Z chromosome is significantly correlated with the S:A ratio. In addition, the degree of degeneration of the Y chromosome may be responsible for the change in the S:A ratio in mammals without a dosage compensation mechanism. Our observations offer unequivocal support for the sex chromosome insensitivity hypothesis in animals and suggest that dosage sensitivity states of sex chromosomes are a major factor underlying different evolutionary strategies of dosage compensation.